(p, 2)-equations resonant at any variational eigenvalue. Issue 7 (2nd July 2020) - Papageorgiou, N. S.; Vetro, C.; Vetro, F.
ABSTRACT: We consider nonlinear elliptic Dirichlet problems driven by the sum of a p -Laplacian and a Laplacian (a ( p, 2 ) -equation). The reaction term at ± ∞ is resonant with respect to any variational eigenvalue of the p -Laplacian. We prove two multiplicity theorems for such equations.